Monitoring System Design of a 4 kWp Off-grid Solar Power Plant - Pudji Muljanto, Widodo; Lomi, Abraham; Putra Muhammad Davi Labib, Radimas; Wahyu Solihin, Muhammad (KnE Social Sciences, 2024)
A monitoring system is needed to determine the performance of an off-grid solar power plant. This paper presents a monitoring system design for an off-grid solar power plant with a capacity of 4 kWp. This off-grid solar power plant system was built on campus 2 of Institut Teknologi Nasional Malang. The purpose of a monitoring system is to collect and present information systematically about the state of the off-grid solar power plant system. This information can be accessed anywhere and anytime by users. Hardware used includes SPM91 to read energy meters digitally, PZEM-017 as a Modbus-based measuring instrument, and communication devices to send data to a database server. The monitoring system dashboard was built using Haiwell SCADA software. The result was a monitoring system that can display parameter data, data loggers, and graphs of the condition of the off-grid solar power plant. The PZEM-017 has an accuracy rate of 99.48% for voltage readings and 98.76% for current readings. Meanwhile, the SPM91 has an accuracy rate of 99.89% for voltage readings and 99.25% for current readings. Keywords: monitoring system, off-grid solar power plant, SCADA software